KEY CHANGES TO THE REGULATION “BRUSSELS I” AND THE FUTURE OF ARBITRATION IN THE CONTEXT OF APPLICATION OF THE REGULATION - Parchajev, Denis; Kisieliauskaitė, Agnė; Bajoraitė, Lina (Teisė, 2016)
This Article focuses on the effects of amendments to the Brussels I Regulation, introduced by its new edition, Brussels I-bis. The analysed amendments are aimed at eliminating the shortcomings of the Regulation’s predecessor. Firstly, the article points out that the new version of the Regulation has solved the issue of unlimited lis pendens and effectively addressed the Italian Torpedo problem. Article 31(2) of Brussels I-bis presents an exception to lis pendens rule, according to which the court, whose exclusive jurisdiction has been agreed upon by the parties, shall have the priority to rule on its jurisdiction regardless of whether other member state courts were seized beforehand. Secondly, the Article explores the new discretion of applying the forum non conveniens doctrine under Articles 33 and 34 of Brussels I-bis. Thirdly, the abolition of exequatur is explained. These innovations address the criticism faced by the previous Regulation head-on by offering a better protection of the rights enshrined in the Regulation, speeding up the work of the judiciary and reducing the litigation costs. On the flipside, these improvements are complimented by certain tangible risks. Therefore additional safeguards may have to be put in place in order to eliminate the possibility of abuse. Particular attention in this Article is paid to novelties in relationship between Brussels I-bis and arbitration. Article 73(2) of Brussels I-bis and Article 12 its Preamble drastically strengthened the position of arbitration in Europe. West Tankers case rationale, which renders the Regulation applicable to preliminary questions of validity of an arbitration agreement and other arbitration-related issues, where the subject-matter of the proceedings comes within the scope of the Regulation, has finally been rejected. Brussels I-bis also expressly provides that recognition and enforcement of arbitration awards shall proceed according to the New York Convention, rather than Brussels I-bis. The practical implications of such changes have already seen the light of day in Advocate General Wathelet’s report in Gazprom case. Comparison of the latter with recent Advocate General Jääskinen’s report in the CDC case clearly outlines a significant shift in the attitude towards arbitration. Mr. Wathelet’s report shows that Brussels I-bis provides arbitration with a much higher degree of autonomy from the Regulation, which makes arbitration a lot more appealing to both businesses and practitioners. Unfortunately, CJEU is yet to confirm the findings of Mr. Wathelet. The Court has shied away from entertaining the questions of the relationship between arbitration and Brussels I-bis in Gazprom judgment. Nevertheless, Mr. Wathelet’s report gives hope that future CJEU judgments will completely forego the West Tankers rationale as far as arbitration is concerned and arbitration community shall celebrate yet another victory.